Effect of Participatory Research on Farmers' Knowledge and Practice of IPM: The Case of Cotton in Benin - TOGBE, CODJO EULOGE; HAAGSMA, REIN; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; VODOUHE, DAVO SIMPLICE (My University, 2014)
ABSTRACT Purpose: This study assesses the effect of participatory research on farmers’ knowledge and practice of Integrated Pest Management (IPM) in Benin. The participatory field experiments were carried out during the 2011–2012 cotton growing season, and focused on the development and application of pest management knowledge. Methodology: A ‘Difference-in-Differences’ methodology was used to document the changes in farmers’ knowledge and practices across the following season, 2012–2013. Of the 180 cotton growers sampled, 150 took part in the research, while 30 served as the control. Findings: Participation in the research increased farmers’ ability to recognise pests and natural enemies and how to use thresholds and apply bio-pesticides. Increase in knowledge did not lead to any modification in the farmers’ use of neem oil and the entomopathogen Beauveria, but it did lead to a significant change in threshold-based pesticide applications. Farmers seemed to want to reduce pest management costs, whatever the type of pesticide recommended (conventional or biobased). Practical Implications: Development practitioners should be aware that changes in practices of IPM are not only knowledge driven. Other factors such as financial consideration and specific input availability are also needed for the success of an effective pest management strategy. Originality/Value: In any interactive process, the Difference-in-Differences methodology is an appropriate tool for an effective assessment of changes in farmers’ knowledge and practices over time.
Keywords: K; EY WORDS: Farmer learning; Pest management; Bio-pesticide; Threshold; Natural enemies; Difference-in-differences.